Merangkul Tradisi, Mengungkap Identitas: Pendekatan Reinventing Tradition dalam Perancangan Bandara Perintis di Kabupaten Batang - Muhammad Ibriza Maghnuni; Tarranita Kusumadewi; Moh Arsyad Bahar (Universitas Sebelas Maret Surakarta, 2023)
Batang Regency is striving to accelerate economic and tourism growth through the Batang Integrated Industrial Zone (KITB) project. One crucial component to support KITB is the availability of public transportation facilities like airport which believed to stimulate economic and tourism growth optimally. Therefore, the design of a pioneer airport terminal is required, serving both as a mode of transportation and an effort to enhance the city branding of Batang Regency. The goal of this design is to initiate a branding strategy through the Reinventing Tradition approach obtained from the triangle architecture semiotics method, the goals is to unearth the values of tradition through a process of hybridization. The result is the design of a pioneer airport terminal that embodies principles such as appreciation, metaphorical meaning, context, interpretation, and performance derived from the culture of Rifa'iyah batik, traditional rowing competitions, Alas Roban, and the local community's character.